Perioperative Morbidity and Mortality of Same-admission Staged Bilateral TKA - Poultsides, Lazaros A. (Clin Orthop Relat Res, 2014)
BACKGROUND: Controversy continues regarding the optimal timing of surgery for patients with symptomatic bilateral degenerative knee arthritis who are not considered eligible for same-day bilateral TKA (BTKA). QUESTIONS/PURPOSES: We compared (1) 30-day mortality; (2) rates of in-hospital complications; and (3) blood transfusion rates between patients undergoing same-admission staged BTKA and patients undergoing BTKA staged within 1 year in a highly specialized center where specific guidelines have been implemented for same-day BTKA patient selection. METHODS: We analyzed institutional data for 149 patients undergoing same-admission staged and 1557 patients undergoing staged BTKA diagnosed with bilateral knee idiopathic osteoarthritis from 1998 to 2011. Although patients in both groups presented with bilateral knee disease, same-admission staged patients had more medical comorbidities and did not qualify for same-day BTKA. Specifically, patients with coronary artery disease with inducible ischemia, congestive heart failure, advanced chronic obstructive pulmonary disease, uncontrolled diabetes, peripheral vascular disease, renal failure, morbid obesity, history of venous thromboembolism, or those who were older than 75 years were not considered eligible for same-day BTKA. Patient demographics and Deyo comorbidity index were tabulated. The groups were similar in age, but same-admission staged patients were more likely to be male and had a higher overall comorbidity burden. The complications were categorized into systemic (medical) and local (orthopaedic). Furthermore, the systemic complications were subcategorized into major (required complex surgical or medical intervention or were deemed life-threatening) and minor (necessitated additional observation or required medical treatment), depending on their severity. Regression models were conducted to examine the association between surgery type and development of complications. RESULTS: There was no difference in 30-day mortality between the groups (0% versus 0.06%; p = 0.754). There was no difference in the local complication rates (0.7% versus 0.8%; p = 1.000). However, multivariable regression analysis adjusting for age, sex, and Deyo comorbidity index showed that same-admission staged patients were three and two times more likely than staged to develop a minor (odds ratio [OR], 3.02; 95% confidence interval [CI], 1.25–3.25; p = 0.004) and major (OR, 2.02; 95% CI, 2.09–4.37; p < 0.001) complication, respectively. The same-admission group experienced more acute postoperative anemia (11% versus 3%; p < 0.001) and blood transfusions (93% versus 54%; p < 0.001). CONCLUSIONS: These results suggest that patients who are not appropriate candidates for same-day BTKA as a result of increased overall comorbidity burden may be better served by undergoing staged BTKA within 1 year rather than same-admission staged because of the associated higher perioperative morbidity observed in the same-admission BTKA group. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.